Improving Arabic Speaking Skills Through Role Play Method in Class - Mohamad Idhan (Journal of Pedagogi, 2025)
Speaking skills in language learning play an important role in everyday communication, but in the context of Arabic language learning, many students face difficulties in speaking due to limited vocabulary, low self-confidence, and lack of authentic interaction. The Role Play method is one of the effective solutions in improving students' speaking skills by providing a more interactive and contextual communication experience. This study aims to analyze the effectiveness of the Role Play method in Arabic language learning through a literature study with a descriptive qualitative approach. The results of the study indicate that the Role Play method, which is based on Communicative Language Teaching (CLT), is able to increase spontaneous speaking, reduce anxiety, and enrich vocabulary and understanding of language structures. Its success depends on relevant scenarios, gradual guidance, and constructive feedback from teachers. However, challenges such as low student self-confidence and limited contextual scenarios are still obstacles in its implementation. Therefore, supportive learning strategies, the use of digital media, and a learning environment that encourages active interaction are needed. With the right approach, the Role Play method can be an effective alternative in improving Arabic speaking skills actively and meaningfully.